A Decade Of Publication: Message From Editor-in-chief - Ooi , Keat (Penerbit Universiti Sains Malaysia (USM Press), 2014)
Head-scratching thoughts to present plausible activities for the Asia Pacific Research Unit (APRU), School of Humanities, Universiti Sains Malaysia of which I was appointed coordinator brought forth the idea of an academic journal. This notion struck me, and on reflection, recalled that I was totally clueless of publishing a journal entailed. Flipping through pages of scholarly journals helped, to some extent, in comprehending the tasks ahead, but on the other hand the said perusing almost dissuaded me from proceeding with what appeared to be a "presumptuous idea." Tapping the minds of others was the next round of action. In London, and later in Hull, the English said "Nay," apparently thought too problematic, sustainability issues, questionable quality; in short, too much hassle. Perhaps publication of an occasional paper series; not tight-down by any specific deadline as journal issues are bounded with, and the "occasional" really means occasional, nothing fixed and/or obligated. The Dutch, however, were encouraging. And in Leiden, the germ of an electronic journal (e-journal) was planted. The concretisation of the idea of a journal gradually emerged while mid-air on the Amsterdam–Kuala Lumpur flight. But it was the tussle between a conventional hard copy version and an e-journal that remained unresolved. The "How" was apparently not questioned, neither in London nor Amsterdam or Leiden thanks to the unquestioned confidence of my AngloDutch circle of friends. The focus then was the concern of the "What," particularly the type of journal in the planning.